Implementation of Duolingo Application in Enhancing Vocabulary Skills of Tenth-Grade High School Students - Marzam, Naya; Kencanawati, Dewi; Riwayatningsih, Rika (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This study investigates the effectiveness of the Duolingo application in improving vocabulary mastery among tenth-grade students at SMAN 3 Kediri. Many EFL learners in Indonesia face challenges transitioning from passive word recognition to active usage, compounded by a lack of engaging, technology-based instruction. The research used a pre-experimental design with pre-test and post-test measurements over a two-week intervention. Students completed daily 15-minute Duolingo sessions focusing on everyday vocabulary topics. Results revealed significant improvement in vocabulary scores, with an average increase of 18% from pre-test to post-test. Qualitative observations also indicated higher engagement and motivation, attributed to Duolingo’s gamification features and multimodal learning approach. The findings highlight the potential of integrating mobile-assisted language learning tools into formal education, especially in contexts where traditional methods dominate. This research contributes to pedagogical strategies for EFL classrooms, emphasizing technology integration to enhance vocabulary retention and active use.